Greenhouse Gas Emissions, Political Visibility and Earnings Quality - Luckmika Perera; Christine Jubb (Australasian Accounting, Business and Finance Journal, 2024)
Using Australian data, this study examines whether there is a significant difference in earnings quality between companies required by the National Greenhouse Gas Energy Reporting (NGER) Act to provide carbon emission disclosures and those not affected by the Act. The Act was implemented across three years from 2009-2011 with decreasing thresholds of emission levels progressively covering more companies in these years The findings reveal that earnings quality (proxied by accruals-based earnings management) of companies affected by the Act is significantly higher than that of companies not affected by the Act. Additional tests reveal that companies reporting under the NGER Act exhibit higher earnings quality than was the case before the companies’ emissions met the reporting requirements. NGER-affected firms also tend to exhibit better earnings quality than a randomly matched sample of firms not affected by the Act. Furthermore, there is a positive relationship between earnings quality and emission levels within the sample of NGER-affected firms. The findings hold when alternative measures of earnings management are considered. The results are consistent with the theory that firms facing political visibility due to high greenhouse gas emissions opt for enhanced financial reporting quality to maintain organizational legitimacy.
Keywords: Greenhouse Gas Emissions; Earnings Management; Earnings Quality; Legitimacy